2019
DOI: 10.1111/jocd.13167
|View full text |Cite
|
Sign up to set email alerts
|

Eyebrow growth pattern analysis in patients with eyebrow hypotrichosis after receiving topical treatment: A retrospective study

Abstract: Background: Differences in growth patterns among the various parts of the eyebrow have been observed. Aims: We aimed to investigate changes in the hair density and diameter and analyze the eyebrow growth pattern of each eyebrow part (head, body, and tail) in patients with eyebrow hypotrichosis over a 24-week course of topical treatment. Patients/Methods: A retrospective study of 48 patients who received treatment with bimatoprost 0.01% was conducted. Patient demographic data were collected; measurements of hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…10,11 However, the diameter of POA hair is greater than that of eyebrow hair. 18 The present study showed that the FTTA hair was significantly thinner than the POA hair, with an average diameter of 67.02 6 11.94 mm. The hair growth rate was another factor affecting patient satisfaction.…”
Section: Discussionsupporting
confidence: 43%
“…10,11 However, the diameter of POA hair is greater than that of eyebrow hair. 18 The present study showed that the FTTA hair was significantly thinner than the POA hair, with an average diameter of 67.02 6 11.94 mm. The hair growth rate was another factor affecting patient satisfaction.…”
Section: Discussionsupporting
confidence: 43%
“…In contrast, approximately 10% of eyebrow hairs are in anagen with a shorter duration of 2-3 months. 3,4 The upper and lower eyelashes have approximately 41% and 15% hairs in anagen, respectively, ranging between 4 and 10 weeks duration. [5][6][7][8] The growth rate of eyebrow and eyelash hair is 0.12-0.15 mm/ day compared with 0.3-0.4 mm/day for scalp hairs.…”
Section: Eyebrow and Eyelash Hair Biologymentioning
confidence: 99%
“…The tail segment has thinner hairs and lower hair density, suggesting that these hairs have the shortest anagen and the lowest follicular stem cell proliferation. 4 This may explain why the lateral third of the eyebrow is most vulnerable to clinically apparent hair loss in several conditions. Each follicular unit of the eyebrow contains a single terminal hair, which differs from scalp follicular units with three to four terminal hairs.…”
Section: Eyebrow and Eyelash Hair Biologymentioning
confidence: 99%
See 2 more Smart Citations